Information Technology, Gifted Education and Talent Development: a Literature Review 2010 to 2021 - Reis, Juliana Teixeira da Camara (2022)
The world society will increasingly depend on talent in the field of Information Technology. Thus, gifted children and young people in Information Technology (IT) will be at the forefront of science, technology, and innovation and act in unknown areas. This literature review aimed to investigate the scenario of the insertion of IT in gifted education and talent development presents in the literature from 2010 to 2021. The literature review took place in three databases (Scopus, Capes website, and ScieLO), the terms searched for articles in English (“talent”, "gifted", “giftedness”, “technology”); and in Portuguese (“altas Habilidades”; “superdotação”; “superdotados”; “tecnologia”). As inclusion criteria, the descriptors should be in the abstract, keywords, or title of national or international articles. A total of 54 articles from 10 countries were found. The data revealed that the studies found investigated the following themes: (a) learning mediated using technological tools; (b) programming logic; (c) STEM/STEAM education; (d) spatial skills. It is important to go beyond what is usually observed in the national literature, whose studies focus on the “use” of tools as mediators of learning and seek technological education and project development.